2020
DOI: 10.1186/s13071-020-3953-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the speed of kill of a novel orally administered combination product containing sarolaner, moxidectin and pyrantel (Simparica Trio™) against induced infestations of Ixodes scapularis on dogs

Abstract: Background: The black-legged (or deer) tick, Ixodes scapularis, commonly infests dogs in the USA and is the vector of important zoonotic pathogens, including Borrelia burgdorferi, the causative agent of Lyme disease. Rapid onset of activity is important in reducing the feeding activity of ticks, thereby reducing the possibility of transmission of infections. The speed of kill of a novel oral combination product, Simparica Trio ™ containing sarolaner, moxidectin and pyrantel was evaluated in a well-controlled l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
2
3
1
Order By: Relevance
“…In this study, the initial 24-h efficacy of Bravecto ® (100%) was similar to that of Simparica TRIO ® (99.5%) (Table 2 ). The Simparica TRIO ® results are similar to those of a previous study that demonstrated 99.4% efficacy against I. scapularis at 24 h post-treatment [ 24 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In this study, the initial 24-h efficacy of Bravecto ® (100%) was similar to that of Simparica TRIO ® (99.5%) (Table 2 ). The Simparica TRIO ® results are similar to those of a previous study that demonstrated 99.4% efficacy against I. scapularis at 24 h post-treatment [ 24 ].…”
Section: Discussionsupporting
confidence: 85%
“…The efficacy of Simparica TRIO ® at 8 and 12 h on Day 28 was only 0% and 27.7%, respectively. Similar to a previous study, a slower residual speed of tick kill efficacy was observed for Simparica TRIO ® -treated dogs, where the efficacy of Simparica TRIO ® against I. scapularis at 8 and 12 h post-infestation on 28 days post-treatment was 3.1%, and 52.2%, respectively [ 24 ].…”
Section: Discussionsupporting
confidence: 83%
“…The first few days after host attachment is a critical time in tick biology and provides a window of opportunity for intervention. Simparica Trio ™ administered to dogs has shown rapid efficacy against I. scapularis, beginning to kill ticks within 8 hours of administration against an existing infestation and providing ≥ 94.2% effectiveness against re-infestations within 24 hours for 28 days [28]. While the studies reported here did not focus on speed of Table 5 Arithmetic mean tick counts and percent efficacy relative to placebo for dogs following one oral treatment with Simparica Trio ™ with existing Rhipicephalus sanguineus infestations and after subsequent weekly re-infestations kill, it is important to note that the efficacy of Simparica Trio ™ was ≥ 98.9% at the first post-treatment evaluations for all five tick species.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is recommended that B. burgdorferi antibody positive dogs be tested for proteinuria due to concerns about the development of potentially fatal kidney disease (Lyme nephritis). Acaricides, including fluralaner and afoxolaner (isooxazoline family), are widely used on dogs and have good efficacy and safety profiles (Allen et al, 2020;Holzmer et al, 2020;Kryda et al, 2020;Petersen et al, 2020). While varying with the product, acaricides can be delivered orally as chewables, topically (so called "spot on" application) or through the use of treated collars.…”
Section: Ld In Companion Animalsmentioning
confidence: 99%